(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the concept of noun predicates within the domain of syntax and pragmatics, analyzing their structural role and communicative function in various discourse contexts. A noun predicate—typically realized in a copular sentence—is crucial in asserting identity, categorization, or description. This paper not only defines and categorizes noun predicates but also focuses on their pragmatic features, including topic-focus articulation, presupposition, and their role in speech acts such as assertion, definition, and classification. Through corpus-based and constructed examples, we examine how noun predicates contribute to information structure, speaker intent, and conversational implicature.